Association of plasma cell subsets in the bone marrow and free light chain concentrations in the serum of monoclonal gammopathy patients. Issue 8 (1st June 2012) - Ayliffe, Michael John; Behrens, Judith; Stern, Simon; Sumar, Nazira
Abstract : This study investigated bone marrow plasma cell subsets and monoclonal free light chain concentrations in blood of monoclonal gammopathy patients. 54 bone marrow samples were stained by double immunofluorescence to enumerate cellular subsets making either intact monoclonal immunoglobulin or free light chains only. Blood taken at the same time was assayed for free light chains by an automated immunoassay. Patients were assigned to three cellular population categories: single intact monoclonal immunoglobulin (59%), dual monoclonal immunoglobulin and free light chain only (31%), or single free light chain only (9%). The median affected free light chain concentration of each group was 75 mg/l, 903 mg/l and 3320 mg/l, respectively, but with substantial overlap. In myeloma patients the difference in serum free light chain concentrations between patients with free light chain only marrow cells and those without was statistically significant. Serum free light chain levels >600 mg/l result mostly from marrow cells restricted to free light chain production.